Comfort Food as Consumer Preference in Purchasing Decisions - Yuliana, Lingga (Widya Cipta - Jurnal Sekretari dan Manajemen, 2024)
This study attempts to determine the comfort food preferences of consumers that are chosen when making selections about purchases. Whereas traditional food, which is a popular choice among consumers, will be the focus of the researcher's case study. The descriptive qualitative method was employed in this investigation. Domain analysis was the analytical approach used in this study. Simple random sampling as a data collection method. 100 residents of Jabodetabek participated in the study as participants. In order discover more about the respondents' choices, a questionnaire is used in this study, and interviews are conducted to elicit more detailed responses. Three respondents were interviewed after the questionnaire was given to 100 respondents by the researchers.The study's findings demonstrate that the younger generation's excitement for traditional cuisine as comfort food is excellent. Price, ease of obtaining food, and the food's characteristic taste are the next factors that affect consumer preferences for comfort food while making purchasing decisions. Culinary entrepreneurs will have opportunity to establish themselves in the food and beverage industry thanks to the comfort food boom. Thus, businesses should find it intriguing to offer classic cuisine varieties that the younger generation is less familiar with as a consumer alternative.These businesspeople's indirect expression of their love for Indonesia's motherland is to make traditional food the centerpiece of their cafes and restaurants. So that people don't solely rely on comfort food from abroad.